Character Building Capital to Avoid Bullying Social Behavior of Elementary School Children Based on Homeschooling - Ayu, Dea Retno; Lestari, Mas Roro Diah Wahyu (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: Bullying in elementary schools is a serious problem that can affect children's social and emotional well-being. This research aims to analyze the character-building capital applied in homeschooling and how this influences the social behavior of elementary school children in the context of bullying prevention. Design/methodology/approach: This study uses a qualitative approach with in-depth interview methods and observations of parents and children participating in homeschooling. Findings: The research results show that homeschooling provides flexibility in the application of character values that can be adapted according to the child's individual needs. Character education methods applied in homeschooling, such as a values-based approach and direct parental involvement, have proven effective in increasing children's empathy, responsibility and social skills. This research provides new insight into the role of homeschooling in character formation and bullying prevention, and offers recommendations for developing more effective character education strategies in the homeschooling context. It is hoped that these findings will contribute to parents, educators and policy makers in creating a safer and more supportive educational environment for these children. Paper type: Research paper